Ferrocenyl catechols : synthesis, oxidation chemistry and anti-proliferative effects on MDA-MB-231 breast cancer cells - Hillard, Elizabeth A. (2013)
The synthesis and anti-tumoral properties of a series of compounds possessing a ferrocenyl group tethered to a catechol via a conjugated system is presented. On MDA-MB-231 breast cancer cell lines, the catechol compounds display a similar or greater anti-proliferative potency (IC50 values ranging from 0.48–1.21 μM) than their corresponding phenolic analogues (0.57–12.7 μM), with the highest activity found for species incorporating the [3]ferrocenophane motif. On the electrochemical timescale, phenolic compounds appear to oxidize to the quinone methide, while catechol moieties form the o-quinone by a similar mechanism. Chemical oxidation of selected compounds with Ag2O confirms this interpretation and demonstrates the probable involvement of such oxidative metabolites in the in vitro activity of these species.